Isolation of GAL Tularemia Bacteriophage and its Characteristics - A. A. Grigor’ev; I. V. Borisevich; I. V. Darmov; V. P. Bondarev; S. L. Kuznetsov; A. V. Mironin; I. P. Pogorelsky; A. V. Letarov; E. E. Koulikov; A. A. Manykin (Проблемы особо опасных инфекций, 2008)
Temperate tularemia bacteriophage was for the first time isolated from the organs of guinea-pig infected with live tularemia vaccine strain N 15 of RIEH line. Negative colonies of bacteriophage were up to 0.2 mm in diameter with incomplete lysis zone at the periphery. In view of the results of electronic microscopy bacteriophage represented filamentous carpuscules. Bacteriophage lyzed bacteria of three subtypes of tularemia etiological agent and bacteria of the main species of legionellosis etiological agents. The simple use of bacteriophage allows to recommend new tularemia bacteriophage GAL for practical application.